Towards Digital Diagnosis of Oral Cancer: A Study on Optimum Preferences of Histopathological Techniques and Features (Medico Legal Update, 2020)
Accurate diagnosis is dependent on various factors in the pathological domain, like types of slides used andfeatures scrutinized. Sometimes a diagnosis is evident due to clear symptoms. But under adverse constraints,like improper acquisition etc., it is very difficult to give a quick and clear diagnosis. The study aims toconduct a survey from the well-known histopathologists of the country to gather an understanding of thetechniques preferably used by them for diagnosis of the disease and summarize it, for arriving at optimumoptions which may be adopted for automation. This was a cross-sectional study conducted from March 2018to May 2018 using a pre-tested structured questionnaire of multiple answer choices. The study subjectscomprised of resident histopathologists of the hospitals covering states/locations all over the country, byselective sampling. The hospitals were selected based on the availability of on-site pathology centres andwide coverage. The analysis of the data was done using Ms-Excel and SPSS. The Non-Parametric FriedmanTest was conducted to test for significance of the responses. Oral Squamous Cell Carcinoma (OSCC) ofbuccal mucosa with both moderately and well-differentiated grades were reported. For diagnosis, H&Estain for the slides of 4? thickness is mostly used. Further, invasion of basement membrane was the mostimportant architectural feature and increased nucleo-cytoplasmic ratio the most important cytologicalfeature. This type of survey will help in carrying out a directed diagnosis or further research for automateddiagnosis using the results.